Pseudo-static tests of reinforced concrete pier columns confined with pre-tensioned superelastic shape memory alloy wires. (1st April 2023) - Qian, Hui; Wu, Peng; Ren, Zepeng; Chen, Guolin; Shi, Yifei
Highlights: A novel self-centering SMA-confined RC composite column was proposed and experimentally tested. Pseudo static tests were conducted on eight specimens of the proposed composite column. Effects of axial compression ratio, SMA pre-strain level, and SMA configuration rate on the seismic performance of the SMA-confined RC columns were investigated. Abstract: To enhance the seismic performance and self-centring capacity of reinforced concrete (RC) pier columns, a novel self-centring shape memory alloy (SMA) wire-confined–RC-composite column was proposed and experimentally tested in this study. One common RC-pier specimen and eight SMA-wire-constrained–RC-pier specimens were constructed for experimentation. The effects of the axial-compression ratio, SMA pre-strain level, and SMA configuration rate on the seismic performance of the RC piers were investigated. The failure mode, hysteresis curve, skeleton curve, bearing capacity, ductility, stiffness, energy-dissipation capacity, and self-centring capacity of the novel column are illustrated and discussed. The test results show that, compared with the shear failure of normal RC-pier columns, the failure mode of the SMA-wire-confined–RC-pier columns were transformed into bending failure or bending-shear failure with certain ductility. With an increase in the SMA-wire configuration rate, the shear bearing capacity, ductility, energy-dissipation capacity, and self-centring capacity of the RC-pier columns were improved. Pre-tensioned SMA wires were attributed to the earlier activation of force restraint and provided a greater binding force, providing more shear restraint and improving the deformation capacity of the core concrete. The ductility and bearing capacity of the strengthened specimens decreased with an excessively large axial-compression ratio; however, they were higher than those of unreinforced specimens. The research results provide new ideas and an experimental basis for the external strength gain and rapid recovery of existing RC piers after an earthquake.